Relação peso-comprimento para peixes de água doce no Brasil: uma revisão sistemática - Rios, Beatriz (2024)
Our objective was to compile data on the length-weight relationship for freshwater fish species in Brazil, which is crucial for fisheries monitoring and management programs, through a systematic review based on the PRISMA protocol. In total, 114 articles were analyzed, covering publications up to 2023. The review revealed a significant increase in the number of publications over time, particularly in the last decade, with peaks in 2014, 2018, and 2019. Among the reviewed articles, estimates of the length-weight relationship were recorded for 787 fish species. Hoplias malabaricus, Pimelodus maculatus, and Astyanax lacustris stood out with the highest number of estimates of the length-weight relationship. Most studies were performed in rivers, with record also available for streams, reservoirs, lakes, ponds, and floodplains. Geographically, the majority of publications focused on the Amazonas Lowlands ecoregion, reflecting its high biodiversity and ecological importance. Estimates for the parameters a and b of the length-weight relationships varied within expected ranges for freshwater fish species. Characiformes and Siluriformes were the orders with the highest number of estimates, highlighting the families Characidae and Loricariidae.